Addressing the vexed issue of authorship and author order: A discussion paper. (8th July 2018) - McCann, Terence V.; Polacsek, Meg
Abstract: Aims: To review and discuss authorship and author order in the context of nursing and midwifery publications and to present a set of principles to guide and justify author order. Background: Variation in author order trends is evident across different authors, disciplines and countries. Confusion and conflict between authors give rise to important issues concerning ethics and collaboration and may delay publication. Lack of transparency in authorship practices also impedes judgements when individual contributions are used in support of employment, promotion, tenure and/or research funding applications. Design: Discussion paper. Data sources: A literature search of BioMed Central, Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE with Full Text and PubMed for original peer‐reviewed papers published in English between 2007 ‐ 2017, in the disciplines of nursing and midwifery. Implications for nursing: Much is written about authorship practices across disciplines and countries. Despite existing authorship guidelines, author order remains an area of confusion and contention. Disputes about authorship and author order have the potential to cause distrust and breakdowns in research relationships, thereby disrupting nursing and midwifery scholarship and research. The main issues concern honorary and ghost authorship, authorship versus acknowledgement, confusion about collaboration, author order, research students as co‐authors, equal author credit and the need for explicit guidelines. Conclusion: Good communication and mutual respect are crucial to the authorship process. However, clear instructions are needed to guide decisions on authorship and author order. It is recommended that the "first‐last‐author‐emphasis" be adopted uniformly internationally across nursing and midwifery research.